Pandemi Covid-19, Kualitas Audit, Biaya Audit, dan Pergantian Auditor - Matitaputty, Jean Stevany (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
The Covid-19 pandemic that has occurred throughout the world has had an impact on the public accounting profession. The Covid-19 pandemic caused the audit process to be carried out to be hampered by the existence of rules regarding social distancing. The research aims to examine the effect of the Covid-19 pandemic on audit quality, audit fees and auditor turnover. The research uses a quantitative method with data on infrastructure, utility and transportation companies listed on the Indonesia Stock Exchange during 2018-2021 using a purposive sampling technique. Data analysis was performed using panel data linear regression and processed using the Eviews 9 application. The results showed that the Covid-19 pandemic had a negative effect on audit quality and a positive effect on auditor turnover. This research contributes to the development of the literature by providing empirical evidence regarding the impact of the Covid-19 pandemic on auditing. Keywords: The Covid-19 pandemic; Audit Quality; Audit fee; Auditor Switching